Bi‐phasic theory vs. volumetric viscoelasticity for modelling the behaviour of thin collagenous membranes. Issue 1 (October 2016) - Stracuzzi, Alberto; Ehret, Alexander E.
Abstract: A relation is established between a recently proposed single‐phase model for human amnion [1], in which an internal state variable accounts for viscoelastic volume changes due to fluid outflow, and an explicitly bi‐phasic representation. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)